If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 + -2 = (x + 8) Reorder the terms: 4 + -2 + 5x = (x + 8) Combine like terms: 4 + -2 = 2 2 + 5x = (x + 8) Reorder the terms: 2 + 5x = (8 + x) Remove parenthesis around (8 + x) 2 + 5x = 8 + x Solving 2 + 5x = 8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 5x + -1x = 8 + x + -1x Combine like terms: 5x + -1x = 4x 2 + 4x = 8 + x + -1x Combine like terms: x + -1x = 0 2 + 4x = 8 + 0 2 + 4x = 8 Add '-2' to each side of the equation. 2 + -2 + 4x = 8 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = 8 + -2 4x = 8 + -2 Combine like terms: 8 + -2 = 6 4x = 6 Divide each side by '4'. x = 1.5 Simplifying x = 1.5
| 6s+(4s-20)=450 | | 7x-3=4-2x | | -6+4(3x-13)=82 | | 2*y-3*y=5 | | 8x+1=1.528 | | -2m-8m=10 | | 24x=24x-27 | | (x+7)2+(y-1)2=32 | | x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 |